2021
DOI: 10.1556/2006.2021.00011
|View full text |Cite
|
Sign up to set email alerts
|

Social media ‘addiction’: The absence of an attentional bias to social media stimuli

Abstract: Background and aimsSocial media use has become a ubiquitous part of society, with 3.8 billion users worldwide. While research has shown that there are positive aspects to social media engagement (e.g. feelings of social connectedness and wellbeing), much of the focus has been on the negative mental health outcomes which are associated with excessive use (e.g. higher levels of depression/anxiety). While the evidence to support such negative associations is mixed, there is a growing debate within the literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…However, when employing a visual search task Johannes et al [ 4 ] found no impairment in performance when SNS logos (either with or without notification signs) were used as distractors compared to non-social iPhone app controls. In line with this study but using a novel and more ecologically valid visual search task, Thomson et al [ 26 ] found no evidence that an attentional bias to SNS logos is correlated with addiction severity. However, while measures of attentional bias have so far not shown clear evidence of altered attentional processing of SNS cues (in both “regular” and compulsive users), these cues might still elicit stronger motivational responses than control cues and/or differentiate motivational responses of regular users from those of compulsive users.…”
Section: Introductionsupporting
confidence: 73%
“…However, when employing a visual search task Johannes et al [ 4 ] found no impairment in performance when SNS logos (either with or without notification signs) were used as distractors compared to non-social iPhone app controls. In line with this study but using a novel and more ecologically valid visual search task, Thomson et al [ 26 ] found no evidence that an attentional bias to SNS logos is correlated with addiction severity. However, while measures of attentional bias have so far not shown clear evidence of altered attentional processing of SNS cues (in both “regular” and compulsive users), these cues might still elicit stronger motivational responses than control cues and/or differentiate motivational responses of regular users from those of compulsive users.…”
Section: Introductionsupporting
confidence: 73%
“…AB towards addiction-related cues is considered to account for the maintenance of the addiction cycle [ 20 , 25 ]. Nikolaidou et al previously found that problematic users of SM tend to show an increased AB towards SM-related stimuli [ 25 ], but contrarily, Thomson et al found that there was no special AB effect towards SM-related cues in problematic users [ 26 ]. The current study was consistent with the former finding.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings support the hypothesis that the AB effect is a common underlying mechanism related to PSMU and other addictions. However, another study by Thomson et al did not provide support for the presence of the AB effect in PSMU [ 26 ]. Their study found that problematic users of SM showed no preferential attentional capture by SM apps and notifications with a visual search paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…The outbreak of COVID-19 has had negative influences on the living state and mental health of teenagers. For the prevention and control of the epidemic, social interaction was forced to transfer online from offline (1), and it induced some negative emotions such as anxiety, depression, and stress (2,3). To relieve negative emotion, most teenagers choose Internet games to cope.…”
Section: Introductionmentioning
confidence: 99%